Catalytic synthesis of distillate-range ethers and olefins from ethanol through Guerbet coupling and etherification. Issue 12 (24th May 2019) - Eagan, Nathaniel M.; Moore, Benjamin M.; McClelland, Daniel J.; Wittrig, Ashley M.; Canales, Emmanuel; Lanci, Michael P.; Huber, George W.
Abstract : Ethanol can be converted to heavy diesel ethers and jet fuel precursor olefins through sequential Guerbet coupling and dehydration. Abstract : Synthesis of distillate-range fuels from biomass-derived alcohols has recently received considerable attention due to projected increases in the demands of these fuels and the extensive commercialization of alcohol production. Here we present a two-stage process by which an alcohol such as ethanol or 1-butanol can be converted with high yields into distillate-range ethers and olefins by combining Guerbet coupling and intermolecular dehydration. The ethers can be used as cetane-improvers in diesel fuel, while the olefins can be hydrogenated and blended with gasoline or oligomerized and hydrogenated to jet-range paraffins. The first stage was executed using calcium hydroxyapatite to produce higher linear and branched alcohols at above 80% selectivity at up to 40% conversion with high stability for over 400 h time-on-stream operation. Increasing conversion decreases selectivity, producing predominantly mono-ene and diene byproducts. Etherification was performed using the acidic resin Amberlyst™ 70 at around 65% conversion. Linear alcohols were converted at above 90% selectivity while branched alcohols were far more selective to olefins (65–75%). Etherification occurs via two mechanisms: a direct mechanism involving the reaction of two alcohols and an indirect mechanism between an alcohol and equilibrated pool of olefins. Cross-etherification was observed between linear and branched alcohols, improving the selectivity to ethers in conversion of the latter. A mixture of C4+ alcohols produced from ethanol condensation at 40% conversion was effectively utilized in etherification at selectivities comparable to the model mixtures. An overall process is presented for the conversion of ethanol to diesel-range ethers and olefins with yields of approximately 80%.